Language learning: human capital investment or consumption? - Matthias Huber; Ann-Marie Sommerfeld; Silke Uebelmesser (Empirica, 2022)
This paper focuses on foreign language learning as human capital investment or consumption. We apply the human capital investment framework to foreign language learning and enlarge it by the consumption motive. Based on a novel dataset of close to 5000 language course participants in 14 countries worldwide, we estimate individual and country-level determinants of the different motives for language learning and of the expected use of language skills in the labour market. We highlight possible spillovers from the consumption motive to a professional use, which emerge mostly in a "tied-mover" context. This provides guidance for targeted language policies.
Keywords: C82; E21; E22; F15; F22; 330; Language learning; New dataset; Human capital investment; Consumption